Anti-HEPP initiatives in Turkey as an example of environmental movement - Ölçek, Abdulsamet (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
As one of the developing countries, Turkey`s demand for energy is increasing. This demand has led Turkey to the use of renewable energy sources after the 2000s. In this context, HEPPs (Hydroelectric Power Plants) have come to the fore in energy production. However, the widespread use of HEPPs has led to an increase in environmental problems. The problems experienced were protested by various social segments and created social opposition in the process. As a result of these protests and social opposition, an anti-HEPP social movement emerged in the context of environmentalism, which is a social movement in Turkey.
Keywords: environmental movements; HEPPs; opposition to HEPP; new social movements; commodification